Terminologi dan Tafsir Pendidikan Kewajiban Mengenakan Hijab pada Wanita dalam Al-Qur'an, Hadist, dan Ijma’ - Nurhakim, Muhamad Syara (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
The hijab and niqab trend in fashion has experienced substantial growth, both offline and online, especially among teenagers. The adoption of hijab is influenced by globalization that brings the impact of modernization, where the phenomenon of hijabers shows a variety of hijab styles that continue to develop following current trends. The purpose of this study is to examine the obligation to wear hijab on women in the interpretation of Islamic law and build a foundation of understanding rooted in the Qur'an, hadith, and ijma'. This research uses a descriptive qualitative research approach, using library research methods to analyze the verses of the Qur'an, Hadith, and the opinions of scholars related to the order to wear the hijab. The findings of the study show that in the Qur'an, there are three different terms used to refer to women's head covering clothing such as ḥijāb, jilbāb, and khimār. Then, the term hijāb comes from the root word hajaba, which etymologically contains the concept of hiding or covering.